Ex Ante Predictability of Stock Returns in a Frontier Market - Nguyen, Khoa (Applied Finance Letters, 2022)
This study reports results on the ex ante predictability of stock returns using real-time stock market data in Vietnam, a frontier market, from June 2008 to June 2021. Countries classified as a frontier market are often known for currency manipulation, financial market illiquidity, and political instability. Despite the enormous risk usually posed by these inefficiencies, potential profits are large and achievable for many investors. This study provides evidence on existing a strategy to form out-of-sample long portfolios that generate statistically significant and positive mean monthly returns even in the presence of transaction costs. I also justify the magnitude of these returns by showing that they exceed those of VnIndex and MSCI Vietnam Index. The results reject the hypothesis that the stock prices in Vietnamese market follow random walks, thus oppose the stock market efficiency hypothesis. Evidence found in this study provides a better understanding of informational efficiency in a frontier equity market setting. Specifically, there are several implications on portfolio selection strategies, stock price patterns, and trading behavior bias related to Vietnamese stock market can be drawn from this study.
Keywords: dept.fin; peer-reviewed

A coronavirus outbreak and sector stock returns: a tale from the first ten weeks of 2020 - Nguyen, Khoa Huu (Applied Economics Letters, 2021)
This paper examines early impacts of the COVID-19 outbreak on stock returns of 11 sectors using the firm-level stock price data from 10 countries. Results show that investors across sectors and countries respond differently during the outbreak. Communication Services, Consumer Staples, Health Care, Information Technology, and Utilities sectors consistently perform relatively well, compared to other sectors, in all countries except Italy, Japan and U.S. Conversely, Energy sector suffers greatest abnormal negative returns, among all sectors, in countries including Canada, Italy, U.K. and U.S. Furthermore, Japan and U.S. have highest numbers of abnormally and negatively affected sectors. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: dept.fin; peer-reviewed

Ex-ante performance of REIT portfolios - Birz, Gene; Devos, Erik; Dutta, Sandip; Nguyen, Khoa; Tsang, Desmond (Review of Quantitative Finance and Accounting, 2022)
The Real Estate Investment Trust (REIT) market has become an increasingly important vehicle for alternative investment for equity investors. While existing research examining the cross-section of REIT returns usually employs standard risk factors in the in-sample models, it can only show the ex-post performance of REIT portfolios. The goal of our paper is to examine the ex-ante performance of REIT portfolios (i.e., the ability of investors to earn abnormal returns in real time). We employ the out-of-sample methodology of Cooper, Gutierrez, and Marcum (2005), and show that ex-ante performance of REIT portfolios is rather weak. For about half of our 19-year sample over the period of 1999 to 2017, the portfolio performances of REITs chosen ex-ante do not beat the performances of the FTSE-NAREIT or the CRSP Equal-Weighted index. After adjusting for transaction costs, the REIT portfolios significantly further underperform their benchmarks. Overall, our findings suggest that the market is relatively efficient in the REIT sector, and it is difficult for investors to devise trading strategies that improve the ex-ante performance of REIT portfolios, based on standard risk factors.
Keywords: Abnormal returns; Out-of-Sample; Portfolio management; Predictability; REITs; Real estate; dept.fin; peer-reviewed